Ensuring Syntactic Interoperability Using Consumer-Driven Contract Testing - Schwarz, Georg Daniel; Quast, Felix; Riehle, Dirk (Software Testing Verification & Reliability, 2025)
Integrating services in service-based architectures is a major concern and challenge to their developers. A key problem is that today's compilers cannot ensure syntactic interoperability of web APIs. Without further help, invalid calls surface only at runtime. Microservice-based architectures exacerbate this problem due to their use of polyglot software stacks and independent deployments. As a result, maintaining API compatibility with consumers has become increasingly complex. This study presents a systematic literature review on consumer-driven contract testing, a testing technique that ensures syntactic compatibility between microservices through isolated test execution. We develop a theory on when and how to use consumer-driven contract testing to address the problem of syntactic interoperability. We build out our theory with the insights of an action research study, contributing rare empirical data to the field. Our theory posits that consumer-driven contract testing can ensure syntactic interoperability between microservices and complement the testing strategy of such systems. The action research study confirmed this and revealed that introducing consumer-driven contract testing can promote the design and development of higher-quality APIs and code.
Created from Fastlane, Scopus look-up
Keywords: action research; consumer-driven contract testing; guidelines; literature review; microservices; testing